From Mary Boas's book, chapter 4.(adsbygoogle = window.adsbygoogle || []).push({});

_{Z = x^3 -e^xy 1- Z(x) = 3x^2 y - ye^xy make sense according to derivation rule d(e^u)/dx = e^u.u` 2-Z(y) = 3^x - xe^xy make sense too. 3-Z(y)x)) = 3x^2 - e^xy - xye^xy where e^xy came from ?? }

Thank you.

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Partial derivation question

**Physics Forums | Science Articles, Homework Help, Discussion**